COMPARISON OF IMMUNOASSAY AND AFFINITY CHROMATOGRAPHY MEASUREMENT OF HbA1c LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS - -, Kevano; Wirawati, Ida Ayu Putri; Lestari, A A Wiradewi (E-Jurnal Medika Udayana; Vol 13 No 11 (2024): E-Jurnal Medika Udayana, 2024)
In 2019, 7.9 million people with type 2 diabetes mellitus in Indonesia were undiagnosed diabetics (73.7%). One of the causes is the lack of diagnostic tools for type 2 diabetes mellitus in primary health care facilities in Indonesia. There are several methods for measuring HbA1c levels, one of which is the immunoassay method used at Sanglah Hospital, Denpasar. Another method that might be an alternative is the affinity chromatography method which is POCT (Point of Care Testing). This study aims to compare the results of HbA1c levels in patients with type 2 diabetes mellitus as measured using immunoassay and affinity chromatography methods. This research is an analytic study with a cross sectional design. The sample in this study consisted of 25 patients with type 2 diabetes mellitus who underwent HbA1c examination at Sanglah Hospital, Denpasar in the period 12 July 2021 to 1 October 2021 and met the inclusion criteria. The remaining blood samples after measuring HbA1c levels using the immunoassay method at Sanglah Hospital Denpasar were then taken to be measured by affinity chromatography method at the Kimia Farma Clinical Laboratory Denpasar. Statistical tests were carried out using the paired sample T-Test method. Paired sample T-Test result shows that the mean levels of HbA1c by immunoassay and affinity chromatography methods are not the same, with the mean difference 0,7760%, 95% CI 0,5058 to 1,0462%, p = 0 There is a significant difference in HbA1c levels in patients with type 2 diabetes mellitus as measured using immunoassay and affinity chromatography methods. Keywords : HbA1c, Immunoassay, Affinity Chromatography